Spatiotemporal regulation by downstream genes of Prok2 in the olfactory system: from development to function - Kim, Bo-Ra; Rha, Min-Seok; Cho, Hyung-Ju; Yoon, Joo-Heon; Kim, Chang-Hoon (Frontiers in Cell and Developmental Biology, 2025)
IntroductionOlfaction is important for the quality of life; however, in Kallmann syndrome (KS), defective development results in olfactory dysfunction. Notably, the mechanism underlying olfactory development, especially in the olfactory epithelium (OE), which detects olfactory signals, remains unclear. Mutations in PROK2, which encodes prokineticin-2, have been identified in approximately 9% of the KS patients with olfactory defects.MethodsWe examined olfactory function and analyzed the causes of olfactory dysfunction based on spatiotemporal development and gene expression changes in Prok2 knockout (KO) model mice with KS.ResultsThe ability of the OE to detect olfactory signals was diminished in adult Prok2 KO mice. Maturation of olfactory sensory neurons (OSNs) in the OE and formation of glomeruli in the olfactory bulb (OB) in adult Prok2 KO mice were disrupted, thus causing olfactory dysfunction. Furthermore, molecular analysis of Prok2 KO mice during embryonic development revealed abnormal development of OB layers and diminished differentiation to mature OSNs in the OE at the later stage, which caused defects in the entire olfactory system. Remarkably, downstream signaling genes of Prok2, including intermediate filament genes and genes expressed in the putative OB, were found to mediate olfactory system organization.DiscussionOverall, these findings reveal the role of Prok2 in olfactory system organization and elucidate how olfactory development defects translate to olfactory function.